LATERAL FLOW ASSAY FOR CRYPTOCOCCAL ANTIGEN: AN IMPORTANT ADVANCE TO IMPROVE THE CONTINUUM OF HIV CARE AND REDUCE CRYPTOCOCCAL MENINGITIS-RELATED MORTALITY - VIDAL, Jose E.; BOULWARE, David R. (Revista do Instituto de Medicina Tropical de São Paulo, 2015)
AIDS-related cryptococcal meningitis continues to cause a substantial burden of death in low and middle income countries. The diagnostic use for detection of cryptococcal capsular polysaccharide antigen (CrAg) in serum and cerebrospinal fluid by latex agglutination test (CrAg-latex) or enzyme-linked immunoassay (EIA) has been available for over decades. Better diagnostics in asymptomatic and symptomatic phases of cryptococcosis are key components to reduce mortality. Recently, the cryptococcal antigen lateral flow assay (CrAg LFA) was included in the armamentarium for diagnosis. Unlike the other tests, the CrAg LFA is a dipstick immunochromatographic assay, in a format similar to the home pregnancy test, and requires little or no lab infrastructure. This test meets all of the World Health Organization ASSURED criteria (Affordable, Sensitive, Specific, User friendly, Rapid/robust, Equipment-free, and Delivered). CrAg LFA in serum, plasma, whole blood, or cerebrospinal fluid is useful for the diagnosis of disease caused by Cryptococcusspecies. The CrAg LFA has better analytical sensitivity for C. gattii than CrAg-latex or EIA. Prevention of cryptococcal disease is new application of CrAg LFA via screening of blood for subclinical infection in asymptomatic HIV-infected persons with CD4 counts < 100 cells/mL who are not receiving effective antiretroviral therapy. CrAg screening of leftover plasma specimens after CD4 testing can identify persons with asymptomatic infection who urgently require pre-emptive fluconazole, who will otherwise progress to symptomatic infection and/or die.